2019
DOI: 10.1093/jb/mvz060
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of the bone trabecula in patients with osteonecrosis of the femoral head by RNA sequencing

Abstract: Early diagnosis and treatment of osteonecrosis of the femoral head (ONFH) is challenging. Bone trabecula play a vital role in the severity and progression of ONFH. In the present study, the investigators used gene expression profiling of bone trabecula to investigate gene alterations in ONFH patients. Osteonecrotic bone trabecula (ONBT) such as necrosis, fibrosis, and lacuna were confirmed by histological examination in the patients. The adjacent ‘normal’ bone trabecula (ANBT) did not show any pathological cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Numerous investigations have demonstrated that hyperlipidemia constitutes a risk factor for ONFH. The risk factors of indicators and hyperlipidemia indicators are examined [ 11 13 ]. Studies have demonstrated that individuals with ONFH commonly exhibit inflammatory reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous investigations have demonstrated that hyperlipidemia constitutes a risk factor for ONFH. The risk factors of indicators and hyperlipidemia indicators are examined [ 11 13 ]. Studies have demonstrated that individuals with ONFH commonly exhibit inflammatory reactions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, phosphatidylcholine metabolism turbulence were detected in FHN rabbit models (Ren et al, 2018). Our previous study also suggested that this disease was related to the disruption of some genes concerning carbohydrate and lipid metabolism (Bai et al, 2019). In addition, previous study also do some endeavors to found out biomarkers for FHN early diagnosis.…”
Section: Introductionmentioning
confidence: 87%